Electrical discharge machining of 6061 aluminium alloy - Pramanik, Alokesh; Basak, A.; Islam, Mohammad Nazrul; Littlefair, G. (2015)
The wire electrical discharge machining (EDM) of 6061 aluminium alloy in terms of material removal rate, kerf/slit width, surface finish and wear of electrode wire for different pulse on time and wire tension was studied. Eight experiments were carried out in a wire EDM machine by varying pulse on time and wire tension. It is found that the material removal rate increases with the increase of pulse on time though the wire tension does not affect the material removal rate. It seems that the higher wire tension facilitates steady machining process, which generates low wear in wire electrode and better surface finish. The surface roughness does not change notably with the variation of pulse on time. The appearance of the machined surfaces is very similar under all the machining conditions. The machined surface contains solidified molten material, splash of materials and blisters. The increase of the pulse on time increases the wear of wire electrode due to the increase of heat input. The wear of wire electrode generates tapered slot which has higher kerf width at top side than that at bottom side. The higher electrode wear introduces higher taper.